Tenets in Microbial Endocrinology: A New Vista in Teleost Reproduction - Haque, Ramjanul; Das, Ipsita Iswari; Sawant, Paramita Banerjee; Chadha, Narinder Kumar; Sahoo, Lakshman; Kumar, Rajesh; Sundaray, Jitendra Kumar (Frontiers in Physiology, 2022)
Climate vulnerability and induced changes in physico-chemical properties of aquatic environment can bring impairment in metabolism, physiology and reproduction in teleost. Variation in environmental stimuli mainly acts on reproduction by interfering with steroidogenesis, gametogenesis and embryogenesis. The control on reproductive function in captivity is essential for the sustainability of aquaculture production. There are more than 3000 teleost species across the globe having commercial importance; however, adequate quality and quantity of seed production have been the biggest bottleneck. Probiotics are widely used in aquaculture as a growth promoter, stress tolerance, pathogen inhibition, nutrient digestibility and metabolism, reproductive performance and gamete quality. As the gut microbiota exerts various effects on the intestinal milieu which influences distant organs and pathways, therefore it is considered to be a full-fledged endocrine organ. Researches on Gut-Brain-Gonad axis (GBG axis) and its importance on physiology and reproduction have already been highlighted for higher mammals; however, the study on fish physiology and reproduction is limited. While looking into the paucity of information, we have attempted to review the present status of microbiome and its interaction between the brain and gut. This review will address a process of the microbiome physiological mechanism involved in fish reproduction. The gut microbiota influences the BPG axis through a wide variety of compounds, including neuropeptides, neurotransmitter homologs and transmitters. Currently, research is being conducted to determine the precise process by which gut microbial composition influences brain function in fish. The gut-brain bidirectional interaction can influence brain biochemistry such as GABA, serotonin and tryptophan metabolites which play significant roles in CNS regulation. This review summarizes the fact, how microbes from gut, skin and other parts of the body influence fish reproduction through the Gut-Brain-Gonad axis.